PERANAN SYEKH BURHANUDDIN DALAM MENGEMBANGKAN AGAMA ISLAM DI NAGARI ULAKAN KECAMATAN ULAKAN TAPAKIS KABUPATEN PADANG PARIAMAN (1683-1704) - Otari, Hayati; Melay, M.Hum, Drs. Ridwan; Ibrahim, M.Si, Dra. Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Purpose of this research is to know and understand how the role of theSyekh Burhanuddin in developing the Islamic religion in the villages Ulakan districtsUlakan Tapakis desert Padang Pariaman. Research done by using historical methods.Data were collected through observation, technical documentation, and interviewtechniques. The results showed that the Syekh Burhanuddin very fought in developing theIslamic religion in the realm of Minangkabau. This can be seen from its success in societyIslamic Ulakan village. Metods used in research this is the method of historical research orhistorically. As for research locations that is in districts Ulakan Tapakis desert PadangPariaman. Time research in starts test proposal to with an examination thesis. Techniquedata collection used the technique observation, the literature study, and interview.Keywords: Role, Syekh Burhanuddin, develop, Islamic religion.